Barriers and facilitators to recruitment of physicians and practices for primary care health services research at one centre - Johnston, Sharon; Liddy, Clare; Hogg, William; Donskov, Melissa; Russell, Grant; Gyorfi-Dyke, Elizabeth (Université d'Ottawa | University of Ottawa, 2010)
Abstract Background While some research has been conducted examining recruitment methods to engage physicians and practices in primary care research, further research is needed on recruitment methodology as it remains a recurrent challenge and plays a crucial role in primary care research. This paper reviews recruitment strategies, common challenges, and innovative practices from five recent primary care health services research studies in Ontario, Canada. Methods We used mixed qualitative and quantitative methods to gather data from investigators and/or project staff from five research teams. Team members were interviewed and asked to fill out a brief survey on recruitment methods, results, and challenges encountered during a recent or ongoing project involving primary care practices or physicians. Data analysis included qualitative analysis of interview notes and descriptive statistics generated for each study. Results Recruitment rates varied markedly across the projects despite similar initial strategies. Common challenges and creative solutions were reported by many of the research teams, including building a sampling frame, developing front-office rapport, adapting recruitment strategies, promoting buy-in and interest in the research question, and training a staff recruiter. Conclusions Investigators must continue to find effective ways of reaching and involving diverse and representative samples of primary care providers and practices by building personal connections with, and buy-in from, potential participants. Flexible recruitment strategies and an understanding of the needs and interests of potential participants may also facilitate recruitment.